Environmental impact of industries on suburban environments - Abbasi, S. A. (Shaid A.); Vinithan, S. (New Delhi Discovery Pub. House, 1997)
With reference to Pondicherry, India, Union Territory.
Includes bibliographical references (p. [143]-145).
Keywords: Industries -- Environmental aspects -- India